Llama Llama loves to read - Dewdney, Anna; Duncan, Reed; Morrow, J. T (New York, New York : Viking, 2018)
Follows Llama Llama throughout the school day as the teacher helps him and his classmates learn how to read.
Keywords: Llamas -- Fiction; Schools -- Fiction; Stories in rhyme